Italian Baroque and Rococo architecture - Varriano, John (Oxford University Press, 1986)
From the late 1500s to the mid-1700s, Italy gave the world some of the liveliest and most imaginative structures in the history of architecture. The first comprehensive study in English of this critical period, this well-illustrated book offers chapters on key architects--Gianlorenzo Bernini, Francesco Borromini, Pietro da Cortona, Guarino Guarini--as well as detailed treatments of the work of many less well-known architects who were active from Sicily to Venice